Design and Build a Face Id-Based Attendance System at Bank Mandiri Sungai Rumbai with the Python Programming Language: Rancang Bangun Sistem Absensi Berbasis Face Id di Bank Mandiri Sungai Rumbai dengan Bahasa Pemograman Python - Burma Ade (Journal of Vocational Education and Information Technology (JVEIT), 2022)
Bank Mandiri Sungai Rumbai is still implementing manual attendance. Then the author has a Face ID-based attendance plan that is more effective during a pandemic like today. Face ID attendance is expected to be useful and can improve employee discipline. The methodology used by the author is the waterfall methodology, this methodology is in the form of an overview, design and manufacture by uniting several separate parts into a unified whole to clarify the form of a system. using the PyCharm application with the Python programming language, where the initial stage of this attendance information system enters the employee's Name and ID, then trains (Training) the employee's face and finally takes attendance (Attendance) by the employee.